Iatrogenic Allogenosis vs. Secondary Allogenosis in Cali, Colombia. A Case Report (2016)
Introduction: Overall, cosmetic surgery has been growing in popularity; likewise, the number of clandestine places that perform these surgeries has increased and, thus, the incidence of complications, morbidity, and direct mortality. Materials and methods: Based on twelve cases assessed between 2009 and 2014 by the Forensic Clinical Group at the Southwestern Regional Office of the National Institute of Legal Medicine and Forensic Sciences, involving patients who underwent some cosmetic surgery related to the use of filling materials, we described the development of disease by biopolymers or iatrogenic allogenosis. Summary of cases: Twelve women underwent aesthetic procedures and developed symptoms and signs of disease by filling substances: pain at injection sites, tumors, and even abscesses in the affected areas Results and discussion: In our report, 100% of the cases were young adult women who had signs and symptoms in common after aesthetic interventions such as buttock augmentation (most common procedure), and even showed manifestations of autoimmunity (autoimmune syndrome/inflammatory syndrome induced by adjuvants). Conclusions: Medical-legal sequels were found in seven of the women, the majority of whom exhibited physical deformity affecting the body and permanent functional disruption of the integumentary organ system. This reflects the danger of allogenic substances (whether approved by the Invima or not) when injected by non-qualified personnel.